URBAN NAMES IN ENGLISH FICTION AND CINEMA DISCOURSE (Philological Studies, 2019)
The article is aimed at analyzing the peculiarities of urban names as markers of a city space in English fiction and cinema discourse from the point of view of urban studies, an actual branch of modern social linguistics and language and culture studies, researching one of the main components of language and cultural situation represented by urban space.
Keywords: urban name, fiction discourse, cinema discourse, language and cultural situation, space parameter